Intra-European Litigation in Eighteenth-Century Izmir The Role of the Merchants' Style - Vanneste, Tijl (Mediterranean Reconfigurations, 2021)
This book offers an account of how merchants litigated on the basis of mercantile custom as well as specific legal procedures, using an ensemble of cases brought before the Dutch consul in Izmir in the second half of the eighteenth century.; Readership: All interested in the legal and socio-cultural tools early modern merchants had at their disposal to ensure the functioning of long-distance and cross-cultural trade. Those interested in European presence in the Ottoman Empire.